Patient predictors and utilization of health services within a medical home for homeless persons. Issue 3 (3rd July 2018) - Jones, Audrey L.; Thomas, Roxanne; Hedayati, Daniel O.; Saba, Shaddy K.; Conley, James; Gordon, Adam J.
ABSTRACT: Background : The Veterans Health Administration (VHA) established a patient-centered medical home model of care for veterans experiencing homelessness called a Homeless Patient Aligned Care Team (HPACT) to improve engagement with primary care and reduce utilization of hospital-based services. To evaluate the impact of the HPACT model, this study compares the number and type of health care visits in the 12 months before and after enrollment in HPACT at one VHA facility, and explores patient characteristics associated with increases and decreases in visits. Methods : Chart reviews of VHA medical records were conducted for all patients enrolled in an HPACT in Pittsburgh, Pennsylvania, between May 2012 and December 2013 ( N = 179). Multivariable mixed-effect logistic regressions estimated differences in having any visit in the 0–6 months and 7–12 months before and after HPACT enrollment, and multinomial logistic regressions predicted increases or decreases versus no change in number of visits over 12 months. Results : Compared with 0–6 months prior to HPACT, patients were more likely to visit primary care in the 0–6 months (adjusted odds ratio [aOR] = 4.91, 95% confidence interval [CI] = 2.94–8.20) and 7–12 months (aOR = 2.30, 95% CI = 1.42–3.72) following HPACT. Patients were less likely to visit the emergency department (ED) or to be hospitalized in the 0–6 months (aOR = 0.57, 95% CI = 0.34–0.94; and aOR = 0.55, 95% CI = 0.25–0.76) and 7–12 months (aOR = 0.43, 95% CI = 0.33–0.91; and aOR = 0.45, 95% CI = 0.26–0.80) following HPACT. Patients were less likely to visit mental health (aOR = 0.35, 95% CI = 0.20–0.60) and addiction specialists (aOR = 0.39, 95% CI = 0.18–0.84) in the 7–12 months following HPACT. Overall, 59% of patients had increases in primary care visits following HPACT. Female patients and those with self-housing were less likely to have increases versus no change in primary care visits (adjusted relative risk ratio [aRRR] = 0.15, 95% CI = 0.03–0.74; and aRRR = 0.35, 95% CI = 0.14–0.90). Conclusions : An integrated HPACT model was successful in engaging homeless veterans in primary care for 1 year, potentially contributing to reductions in ED use. More tailored approaches may be needed for vulnerable populations experiencing homelessness, including homeless women.